WORKSHOP PEMBUATAN PUPUK ORAGANIK CAIR (POC) DARI BAHAN SAMPAH ORGANIK RUMAH TANGGA DI DESA PANDEYAN, NGEMPLAK, BOYOLALI - Agus Mukholid; Elfa Astriyana; Santi Al Munawarah; Raditya Anung Estiawan; Atika Hapsari; Maygita Serli Oktavia; Amalia Nuril Firdaus; Hilmy Fajrian; Rizal Arifudin; Rolas R. Sianturi; Adhelyn Ramadhani (Universitas Pahlawan Tuanku Tambusai, 2023)
Household organic waste is a type of waste that can be reprocessed by utilizing waste into a useful product that functions for plant survival. The geographical conditions of the Pandeyan Village area are the background for the many establishments of house-yard plants by villagers. Plants that are widely cultivated are agricultural crops, food crops, horticultural crops, ornamental plants, and so on. Reusing vegetables as organic waste to be directed to plants owned by residents of Pandeyan Village, Boyolali. This training aims to increase knowledge about the utilization or reprocessing of commonly found organic wastes such as vegetables with products that are more beneficial for the residents of Pandeyan Village. Keywords : Pandeyan, organic waste, fertilizer